Karamat Bukhari's Poetry Collection "Tashnagi" in the context of Ilum ul Bayan o Badie - Siraj, Bismina; Rashid, Robina; Parveen, Nazia (sourcecoder, 2022)
Karamat Bukhari is a renowned poet and literary figure. Although it is really an arduous task for a civil servant to make a name for him/herself in the field of literature, but Karamat Bukhari did it with ease due to his sheer hard work and as a result, gained immense fame. Each of his poetry collection reflects art of the highest quality. He decorated his poetry with fine delicacies of poetic expressions in his poetic collection “Tashnagi”. He has expressed his thoughts and feelings in his poetry with such originality that they tend to induce the same emotions in the readers’ minds that were a mark of his imaginations before putting them out on a piece of paper.